Improving the quality of teaching through learning technology. Didactic mediation and research perspectives - Daniela Maccario (Firenze University Press, 2019)
The use of learning technology in teaching may not appear to have any particularly positive impact on learning itself. One element that could prove to be a game-changer - and one that didactic research is called to look at in-depth - seems to be teacher mediation, which can valorize the communicative potential of technological channels and languages along with the other forms of language used in teaching. This article sets out to analyse the potential contributions of the didactic mediation theories that have developed over the last thirty years in the North American and European francophone context and in Italy. We outline the perspectives that didactic mediation research has opened up regarding the importance of studying didactic mediation from the point of view of teachers' practices. We shall look at the theory of didactic mediators and dwell on the construction of didactic devices through which we will be able to analyse the current and potential use of educational technologies in schools.  Migliorare la qualità dell'insegnamento attraverso le tecnologie per apprendere. Mediazione didattica e prospettive di ricerca L'impiego delle tecnologie per apprendere nell'insegnamento non sembra rappresentare in sé un valore aggiunto significativo rispetto all'impatto sull'apprendimento. Un elemento che può fare la differenza, che la ricerca didattica è chiamata ad approfondire, sembra essere costituito dalla mediazione del docente, che può valorizzare il potenziale comunicativo dei canali e dei linguaggi tecnologici in sinergia con le altre forme di linguaggio in uso nell'insegnamento. L'articolo si propone di analizzare gli apporti che possono derivare dalle teorie della mediazione didattica che si sviluppano nel trentennio scorso in ambito francofono nord-americano ed europeo e nel nostro contesto nazionale. Si delineano le prospettive aperte dalle ricerche sulla mediazione didattica in riferimento all'esigenza di studiare l'insegnamento dal punto di vista delle pratiche dei docenti. Si tratteggia la teoria dei mediatori didattici e ci si sofferma sul costrutto di dispositivo didattico, in relazione al quale analizzare l'impiego di fatto e possibile delle tecnologie per apprendere nella scuola.